Calorimetric Methods for Measuring Stability and Reusability of Membrane Immobilized Enzymes. Issue 2 (26th December 2017) - Mason, Marco; Scampicchio, Matteo; Quinn, Colette F.; Transtrum, Mark K.; Baker, Nicholas; Hansen, Lee D.; Kenealey, Jason D.
Abstract : Abstract: The aim of this work is to develop calorimetric methods for characterizing the activity and stability of membrane immobilized enzymes. Invertase immobilized on a nylon‐6 nanofiber membrane is used as a test case. The stability of both immobilized and free invertase activity was measured by spectrophotometry and isothermal titration calorimetry (ITC). Differential scanning calorimetry was used to measure the thermal stability of the structure and areal concentration of invertase on the membrane. This is the 1st demonstration that ITC can be used to determine activity and stability of an enzyme immobilized on a membrane. ITC and spectrophotometry show maximum activity of free and immobilized invertase at pH 4.5 and 45 to 55 °C. ITC determination of the activity as a function of temperature over an 8‐h period shows a similar decline of activity of both free and immobilized invertase at 55 °C. Practical Application: Enzyme‐catalyzed reactions occur in mild and environmentally friendly conditions, but are usually too costly to use in food manufacturing. When free enzymes are used, they are used once and replaced for each reaction, but enzymes immobilized on a solid support can be reused and have the additional advantage of being removed from the product. In this study, new calorimetric methods that are universally applicable to characterizing immobilized enzymes are used to determine the activity, stability, and reusability of invertase immobilized on a nanofiber support.